Socialization of Literacy Culture as an Effort to Understand Pancasila Values ​​at Al-Amin Orphanage - Jamilah, Jamilah; Adelin, Fitra Surya (Fakultas Kewirausahaan Universitas Garut, 2025)
This article aims to describe the role of literacy culture socialization in enhancing the understanding and internalization of Pancasila values among children in orphanages. The research method employed a descriptive qualitative approach with observation, interviews, and documentation techniques. The findings reveal that literacy activities not only improve reading and writing skills but also instill Pancasila values such as mutual cooperation, tolerance, discipline, and social justice. Thus, literacy culture socialization can be an effective strategy in fostering character education for orphanage children.